2006
DOI: 10.1159/000094804
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a de novo complex chromosome rearrangement (CCR) involving chromosomes 2 and 12, associated with mental retardation and impaired speech development

Abstract: We report on a currently six-year-old patient with a de novo complex chromosome rearrangement (CCR) involving chromosomes 2 and 12. A translocation 2;12 that appeared to be reciprocal after standard banding turned out to be a complex event with seven breaks after molecular cytogenetic analyses. Array CGH analysis showed no imbalances at the breakpoints but revealed an additional microdeletion of about 80 kb on chromosome 11. The same deletion was also present in the phenotypically normal father. The patient sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Highly complex chromosome aberrations with multiple breakpoints have recently been reported in numerous patients (e.g. [Houge et al, 2003; Schwarzbraun et al, 2006; Sensi et al, 2008; Ballarati et al, 2009; Poot et al, 2010]), but the underlying mechanisms of such rearrangements remained largely elusive. Also in the present case we have failed to identify any conspicuous features of chromosome architecture, for example, the presence of homologous segmental duplications at the breakpoints on chromosomes 2, 4, and 5 that could give some hint on the underlying mechanism of this complex interchromosomal rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Highly complex chromosome aberrations with multiple breakpoints have recently been reported in numerous patients (e.g. [Houge et al, 2003; Schwarzbraun et al, 2006; Sensi et al, 2008; Ballarati et al, 2009; Poot et al, 2010]), but the underlying mechanisms of such rearrangements remained largely elusive. Also in the present case we have failed to identify any conspicuous features of chromosome architecture, for example, the presence of homologous segmental duplications at the breakpoints on chromosomes 2, 4, and 5 that could give some hint on the underlying mechanism of this complex interchromosomal rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Given the tiling nature of our BAC clones across the genome, the theoretical resolution of our array is about 75 kb. Although we have shown that this resolution can also be reached in reality [Motazacker et al, 2007;Schwarzbraun et al, 2006], the conservative CNV calling procedure applied in this study resulted in an average functional resolution of about 142 kb as inferred from the mean size of the smallest 10% of CNVs identified in this study. An independent test confirming the reliability of this platform and CNV calling procedure has been published recently [LaFramboise et al, 2009].…”
Section: Array-cghmentioning
confidence: 73%
“…Real‐time PCR was performed as previously described [Schwarzbraun et al, 2006b] and showed that the GCK gene was deleted by a de‐novo mutation, as both her healthy parents did not show a deletion in this genomic segment. Using STR‐marker analysis with markers located within the deletion region we could confirm that the deletion occurred on the paternal allele.…”
Section: Methods and Resultsmentioning
confidence: 99%